Evaluation of porosity in 3D printed trabecular bone structures for prostheses. Issue 1 (October 2021) - Buj, I; Bagheri, A; Ferrer, M; Domínguez, A
Abstract: Hip prostheses require an external porous area in order to fix them by means of osseointegration. Different structures can be printed in order to favour bone fixation, such as octet-truss or trabecular, among others. In the present paper, bone-like structures are printed in cubic shapes, by means of fused filament fabrication (FFF). Three design parameters of the structures were varied: the number of joining points per unit volume, the area scale and the offset that is given to the different struts of the structure. Both the theoretical and the measured porosity of the samples is evaluated, from the drawing of the structures and by means of weight measurements respectively. As expected, the structures having fewer union points per unit volume are more porous than the structures having more points. When low number of points generating struts of the structure were employed, measured porosity is lower than the theoretical one, while when high number of points is considered, the opposite situation is found. The present work will help to obtain porous structures to be used in prostheses, by means of extrusion 3D printing processes.